Nitroimidazoles : synthesis and anti-HIV evaluation of new 5-substituted piperazinyl-4-nitroimidazole derivatives - Al-Soud, Yaseen A. (Array, 2007)
A series of 2-alkylthio-1-[4-(1-benzyl-2-ethyl-4-nitro-1H-imidazol-5-yl)-piperazin-1-yl]ethanones (3-9) and alkyl-[4-(1-benzyl-2-ethyl-4-nitro-1H-imidazol-5-yl)-piperazin-1-yl)ketones (11-20) as well as the indole analogue 22 were synthesized from 4-nitro-5-piperazinyl imidazole derivative 1, with the aim to develop new non-nucleoside reverse transcriptase inhibitors (NNRTIs). The newly synthesized compounds were assayed against HIV-1 and HIV-2 in MT-4 cells. Compound 2 showed inhibition of HIV-1 (EC50 0.45 µg mL-1) and HIV-2 (0.50 µg mL-1), while 9 showed inhibition of HIV-1 (EC50 2.48 µg mL-1, SI = 4)